2017
DOI: 10.1159/000480371
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-222 Promotes the Proliferation of Pulmonary Arterial Smooth Muscle Cells by Targeting P27 and TIMP3

Abstract: Background/Aims: Aberrant vascular smooth muscle cell (VSMC) proliferation plays an important role in the development of pulmonary artery hypertension (PAH). Dysregulated microRNAs (miRNAs, miRs) have been implicated in the progression of PAH. miR-222 has a pro-proliferation effect on VSMCs while it has an anti-proliferation effect on vascular endothelial cells (ECs). As the biological function of a single miRNA could be cell-type specific, the role of miR-222 in pulmonary artery smooth muscle cell (PASMC) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…The activation of the α-SMA promoter may be due, at least in part, to the recruitment and interaction (direct or indirect) of acquired SRF with endogenous class I bHLH factors, which lends further support for a functional cooperation between SRF and class I bHLH factors in the regulation of SM-actin transcription [13,40]. We found that SRF increased with Gal-3 treatment in PAECs, while after SRF knockdown, Gal-3-induced α-SMA expression was decreased.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The activation of the α-SMA promoter may be due, at least in part, to the recruitment and interaction (direct or indirect) of acquired SRF with endogenous class I bHLH factors, which lends further support for a functional cooperation between SRF and class I bHLH factors in the regulation of SM-actin transcription [13,40]. We found that SRF increased with Gal-3 treatment in PAECs, while after SRF knockdown, Gal-3-induced α-SMA expression was decreased.…”
Section: Discussionmentioning
confidence: 75%
“…3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) was used to measure cell viability using the standard method as previously described [12][13].…”
Section: Mttmentioning
confidence: 99%
See 1 more Smart Citation
“…This change in vascular morphology subsequently causes increased pulmonary vascular resistance and decreased vascular compliance, which imposes a hemodynamic load on pulmonary artery pressure. Studies from various teams and our lab have indicated that abnormal cellular proliferation, migration and apoptosis of pulmonary artery smooth muscle cells (PASMCs) are closely associated with vascular remodeling in PAH [7][8][9][10]. Excessive proliferation and apoptosis resistance result in expansion of the PASMC population, while migration of PASMCs further causes arterial muscularization, vessel stenosis and increased vascular tension.…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that proliferation and migration of pulmonary arterial smooth muscle cells (PASMCs) is a critical process underlying pulmonary vascular remodeling in HPH [4][5][6]. Therefore, attenuation of PASMC proliferation and pathogenic vascular remodeling is critical for both the prevention and treatment of HPH [7].…”
Section: Introductionmentioning
confidence: 99%